Copolyester composition with low coefficient of friction
By incorporating additives such as wax and organic siliconane in the polymer composition, the friction coefficient is reduced, and the impact toughness is used to use anti -flushing agents to solve the problem of high friction coefficients of the existing polymer composition, realizing more Extensive application of applicability and performance improvement.
Patent Information
- Application Number
- CN202380046780.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-24
AI Technical Summary
Existing TMCD and EG-based polymer compositions have high coefficient of friction, resulting in unsuitable products in certain durability applications and other physical properties tend to decline when surface properties are adjusted by additives.
The coefficient of friction of the polymer composition is reduced by incorporating friction additives such as waxes and organosiloxanes, while impact toughness is improved using reactive and/or non-reactive impact modifiers.
While maintaining or improving the impact toughness, the friction coefficient is significantly reduced, so that the polymer composition shows a stable friction response within the extensive contact pressure and geometric shape range, similar to the traditional engineering polymer.
Smart Images

Figure BDA0005184962120000301 
Figure BDA0005184962120000302 
Figure BDA0005184962120000311
Abstract
Description
Field of the Invention
[0001] The present invention is generally in the field of polymer science. In particular, the present invention relates to certain copolyesters having low surface energy. Background of the Invention
[0003] High molecular weight thermoplastic linear copolyesters can generally be formed by reacting one or more diesters with one or more diols under suitable polymerization conditions. Specific copolyesters useful for a wide variety of applications can be formed by reacting a diester composition comprising a dialkyl ester of terephthalic acid with a diol composition comprising a first diol component comprising 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) and a second diol component comprising ethylene glycol (EG).
[0004] These copolyesters offer a desirable combination of performance parameters such as toughness, glass transition temperature, density, crystallization rate, melt viscosity and chemical resistance, resulting in numerous benefits to product manufacturers and consumers who purchase these products. However, in the ongoing effort to expand the sale, use and applicability of compositions containing these copolyesters into new markets, polymer manufacturers seek to tailor composition characteristics and parameters to meet product manufacturer specifications in heretofore unexplored product applications.
[0005] Copolyesters based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) and ethylene glycol (EG) can have moderate to high surface energies. High surface energies can be advantageous for certain secondary operations (e.g., weldability, coatability, etc.), however polymer articles made from compositions based on such copolyesters may have moderate to high coefficients of friction (COF). Excessively high COF and low impact toughness may result in polymer articles that are unsuitable for durability applications requiring repeated material-to-material interactions within a range of contact pressures. Manipulation of polymer surface properties, such as coefficient of friction, by incorporation of additives may result in a correspondingly large decrease in other physical properties, or result in trade-offs in base resin properties.
[0006]
[0006] Therefore, a need exists for improved polymer compositions based on TMCD and EG having a reduced coefficient of friction without compromising other desirable qualities of the polymer compositions and durable articles made therefrom. Summary of the invention
[0007] The present invention provides a means for reducing the friction of copolyesters comprising TMCD and EG residues while substantially maintaining or improving impact toughness by incorporating various additives. In one embodiment, the reduction in coefficient of friction is achieved by incorporating additives including certain waxes and organosilicone, while impact modification is achieved by incorporating a wide variety of reactive and / or non-reactive impact modifiers. In addition, certain embodiments of the present invention also maintain clarity while improving impact toughness and reducing the coefficient of friction.
[0008] The friction modified, impact toughened polymer compositions of the present invention containing TMCD and EG residues exhibit tunable friction profiles comparable to those of conventional engineering polymers such as acrylonitrile-butadiene-styrene polymers (ABS) or polycarbonate, and are capable of exhibiting similar friction responses (static and dynamic friction coefficients) over a wide range of contact pressures and part geometries. However, it is noteworthy that physical properties such as heat distortion temperature (HDT) and flexural modulus are maintained after modification, while impact toughness is significantly improved compared to the unmodified copolyester composition.
[0009] In an embodiment, a polymer composition is provided, comprising a copolyester, one or more additives in an amount sufficient to reduce the coefficient of friction (COF) of the polymer composition, and one or more additives in an amount sufficient to increase impact toughness. The copolyester may comprise: a dicarboxylic acid component comprising terephthalic acid residues and a diol component comprising: 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and ethylene glycol (EG) residues; an intrinsic viscosity of 0.1 to 1.2 dL / g, as measured at a concentration of 0.5 g / 100 ml in 60 / 40 (weight / weight) phenol / tetrachloroethane at 25°C; and a glass transition temperature (Tg) of 85°C to 200°C. The one or more additives for reducing COF may be selected from waxes and silicones.
[0010] Additives for friction modification may include small molecule waxes to high molecular weight organosilicones. In embodiments, the additive may be incorporated at a loading of 0.1 wt % to 12 wt % depending on the friction additive selected.
[0011] In embodiments, the one or more additives for increasing impact toughness may be selected from elastomeric compounds or polymers, which serve to absorb or dissipate the kinetic energy of an impact. DETAILED DESCRIPTION
[0012] In a first aspect, the present invention provides a polymer composition comprising:
[0013] (a) a copolyester comprising: (i) dibasic acid residues comprising from about 90 to 100 mole percent terephthalic acid residues and from 0 to about 10 mole percent isophthalic acid residues; and (ii) diol residues comprising from 58 to 95 mole percent ethylene glycol residues; and from 5 to 42 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, wherein the copolyester comprises a total of 100 mole percent of the dibasic acid residues and a total of 100 mole percent of the diol residues.
[0014] (b) from about 0.1 to about 12 weight percent of a friction additive selected from waxes and silicones; and
[0015] (c) from about 0.5 to about 15 weight percent of at least one impact modifier.
[0016] As used herein, the term "polyester" is intended to include "copolyesters" and should be understood to mean a synthetic polymer prepared by the reaction of one or more difunctional carboxylic acids and / or polyfunctional carboxylic acids with one or more difunctional hydroxy compounds and / or polyfunctional hydroxy compounds (e.g., branching agents). Typically, the difunctional carboxylic acid can be a dicarboxylic acid, and the difunctional hydroxy compound can be a dihydric alcohol, such as a diol and a diol. The term "diol" as used herein includes, but is not limited to, diols, diols and / or polyfunctional hydroxy compounds, such as branching agents. As used herein, the term "residue" means any organic structure incorporated into a polymer by polycondensation and / or esterification of the corresponding monomers. As used herein, the term "repeat unit" means an organic structure having a dicarboxylic acid residue and a diol residue bonded by an ester group. Thus, for example, a dicarboxylic acid residue can be derived from a dicarboxylic acid monomer or its associated acyl halide, ester, salt, anhydride and / or mixtures thereof. In addition, as used herein, the term "diacid" includes polyfunctional acids, such as branching agents. Thus, as used herein, the term "dicarboxylic acid" is intended to include dicarboxylic acids and any derivatives of dicarboxylic acids, including their associated acyl halides, esters, half-esters, salts, half-salts, anhydrides, mixed anhydrides and / or mixtures thereof, which can be used in the reaction process with diols to prepare polyesters. As used herein, the term "terephthalic acid" is intended to include terephthalic acid itself and its residues, and any derivatives of terephthalic acid, including its associated acyl halides, esters, half-esters, salts, half-salts, anhydrides, mixed anhydrides and / or mixtures thereof, or residues thereof, which can be used in the reaction process with diols to prepare polyesters.
[0017] The polyesters used in the present invention can generally be prepared from dicarboxylic acids and diols, which react in substantially equal proportions and are incorporated into the polyester polymer as their respective residues. Thus, the polyesters of the present invention may contain substantially equal molar proportions of acid residues (100 mole %) and diol (and / or polyfunctional hydroxy compound) residues (100 mole %), such that the total number of moles of repeating units is equal to 100 mole %. Thus, the mole percentages provided in the present invention may be based on the total number of moles of acid residues, the total number of moles of diol residues, or the total number of moles of repeating units.
[0018] In certain embodiments, terephthalic acid or its esters (e.g., dimethyl terephthalate) or a mixture of terephthalic acid residues and their esters may constitute part or all of the dicarboxylic acid component used to form the polyesters useful in the present invention. In certain embodiments, terephthalic acid residues may constitute part or all of the dicarboxylic acid component used to form the polyesters useful in the present disclosure. For the purposes of the present disclosure, the terms "terephthalic acid" and "dimethyl terephthalate" are used interchangeably herein.
[0019] Can use terephthalic acid ester and other dicarboxylic acids or their corresponding ester and / or salt to replace dicarboxylic acid.Suitable example of dicarboxylic acid ester includes but not limited to dimethyl ester, diethyl ester, dipropyl ester, diisopropyl ester, dibutyl ester and diphenyl ester.In one embodiment, ester is selected from at least one of following: methyl ester, ethyl ester, propyl ester, isopropyl ester and phenyl ester.
[0020] In certain embodiments, the polyester composition comprises a copolyester comprising: (a) dibasic acid residues comprising about 90 to 100 mole percent TPA residues and 0 to about 10 mole percent IPA residues; and (b) diol residues comprising 58 to 95 mole percent EG residues; and 5 to 42 mole percent TMCD residues, wherein the copolyester comprises a total of 100 mole percent of the dibasic acid residues and a total of 100 mole percent of the diol residues.
[0021] In an embodiment, the copolyester comprises diol residues comprising 10 to 42 mole percent TMCD residues and 58 to 90 mole percent EG residues. In one embodiment, the copolyester comprises diol residues comprising 5 to 40 mole percent TMCD residues and 60 to 95 mole percent EG residues.
[0022] In an embodiment, the copolyester comprises diol residues comprising 20 to 37 mole percent TMCD residues and 63 to 80 mole percent EG residues. In one embodiment, the copolyester comprises diol residues comprising 22 to 35 mole percent TMCD residues and 65 to 78 mole percent EG residues.
[0023] In an embodiment, the copolyester comprises: a) a dicarboxylic acid component comprising: (i) 90 to 100 mole % of terephthalic acid residues; and (ii) from about 0 to about 10 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 10 to about 27 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and (ii) from about 90 to about 73 mole % of ethylene glycol residues; and wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %; and wherein the polyester has an intrinsic viscosity (IV) of 0.50 to 0.8 dL / g, as measured at a concentration of 0.25 g / 50 ml in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25° C.; and wherein the polyester has an L* color value of 90 or greater, as measured by ASTM D The polyester has an L* color value greater than 90 as measured by the L*a*b* color system measured in accordance with ASTM D 6290-98 and ASTM E308-99, the measurement being performed on polymer particles ground to pass through a 1 mm sieve. In an embodiment, the polyester has an L* color value greater than 90 as measured by the L*a*b* color system measured in accordance with ASTM D 6290-98 and ASTM E308-99, the measurement being performed on polymer particles ground to pass through a 1 mm sieve.
[0024] In certain embodiments, the diol component of the copolyester comprises: (i) from about 15 to about 25 mole percent of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and (ii) from about 85 to about 75 mole percent of ethylene glycol residues; or (i) from about 20 to about 25 mole percent of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and (ii) from about 80 to about 75 mole percent of ethylene glycol residues; or (i) from about 21 to about 24 mole percent of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and (ii) from about 76 to about 79 mole percent of ethylene glycol residues.
[0025] In one embodiment, the copolyester comprises:
[0026] (a) a dicarboxylic acid component comprising:
[0027] (i) from about 90 to about 100 mole percent of terephthalic acid residues;
[0028] (ii) from about 0 to about 10 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and
[0029] (b) a diol component comprising:
[0030] (i) from about 10 to about 27 mole percent of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues; and
[0031] (ii) from about 73 to about 90 mole percent ethylene glycol residues, and
[0032] (iii) less than about 5 mole % or less than 2 mole % of any other modifying glycol;
[0033] wherein the total mole % of the dicarboxylic acid component is 100 mole %, and
[0034] wherein the total mole % of the diol component is 100 mole %; and
[0035] The copolyesters have an intrinsic viscosity of 0.50 to 0.8 dL / g as measured at a concentration of 0.25 g / 50 ml in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25°C.
[0036] In an embodiment, the copolyester has at least one of the following properties selected from the group consisting of: a Tg of about 90°C to about 108°C, as measured by a TA 2100 thermal analyzer at a scan rate of 20°C / min; a flexural modulus at 23°C of greater than about 2000 MPa (290,000 psi), as defined by ASTM D790; and a notched Izod impact strength of greater than about 25 J / m (0.47 ft-lb / in), as measured according to ASTM D256 using a 1 / 8 inch thick bar at 23°C with a 10 mil notch. In one embodiment, the copolyester has an L* color value of 90 or greater or greater than 90, as determined by the L*a*b* color system measured in accordance with ASTM D6290-98 and ASTM E308-99, the determination being made on polymer particles ground to pass through a 1 mm screen.
[0037] In one embodiment, the copolyester further comprises: (II) a catalyst / stabilizer component comprising: (i) titanium atoms in the range of 10-50 ppm based on the weight of the polymer, (ii) optionally, manganese atoms in the range of 10-100 ppm based on the weight of the polymer, and (iii) phosphorus atoms in the range of 10-200 ppm based on the weight of the polymer. In one embodiment, the 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues are a mixture comprising more than 50 mole % of cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol residues and less than 50 mole % of trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol residues.
[0038] In embodiments, the glycol component of the copolyester may include, but is not limited to, at least one of the following combinations of ranges: about 10 to about 30 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 90 to about 70 mole percent ethylene glycol; about 10 to about 27 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 90 to about 73 mole percent ethylene glycol; about 15 to about 26 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 85 to about 74 mole percent ethylene glycol; about 18 to about 2 6 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 82 to about 77 mole % ethylene glycol; about 20 to about 25 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 80 to about 75 mole % ethylene glycol; about 21 to about 24 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 79 to about 76 mole % ethylene glycol; or about 22 to about 24 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 78 to about 76 mole % ethylene glycol.
[0039] In certain embodiments, the copolyesters may exhibit at least one of the following intrinsic viscosities as measured at a concentration of 0.25 g / 50 ml in 60 / 40 (weight / weight) phenol / tetrachloroethane at 25° C.: 0.50 to 0.8 dL / g; 0.55 to 0.75 dL / g; 0.57 to 0.73 dL / g; 0.58 to 0.72 dL / g; 0.59 to 0.71 dL / g; 0.60 to 0.70 dL / g; 0.61 to 0.69 dL / g; 0.62 to 0.68 dL / g; 0.63 to 0.67 dL / g; 0.64 to 0.66 dL / g; or about 0.65 dL / g.
[0040] In certain embodiments, the Tg of the copolyester may be selected from one of the following ranges: 85°C to 100°C; 86°C to 99°C; 87°C to 98°C; 88°C to 97°C; 89°C to 96°C; 90°C to 95°C; 91°C to 95°C; 92°C to 94°C.
[0041] In another embodiment, the copolyester comprises diol residues comprising 30 to 42 mole percent TMCD residues and 58 to 70 mole percent EG residues. In one embodiment, the copolyester comprises diol residues comprising 33 to 38 mole percent TMCD residues and 62 to 67 mole percent EG residues.
[0042] In an embodiment, the copolyester comprises: a) a dicarboxylic acid component comprising: (i) 90 to 100 mole % of terephthalic acid residues; and (ii) from about 0 to about 10 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 30 to about 42 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and (ii) from about 70 to about 58 mole % of ethylene glycol residues; and wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %; and wherein the polyester has an intrinsic viscosity (IV) of 0.50 to 0.70 dL / g, as measured at a concentration of 0.25 g / 50 ml in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25° C.; and wherein the polyester has an L* color value of 90 or greater, as measured by ASTM D The polyester has an L* color value greater than 90 as measured by the L*a*b* color system measured in accordance with ASTM D 6290-98 and ASTM E308-99, the measurement being performed on polymer particles ground to pass through a 1 mm sieve. In an embodiment, the polyester has an L* color value greater than 90 as measured by the L*a*b* color system measured in accordance with ASTM D 6290-98 and ASTM E308-99, the measurement being performed on polymer particles ground to pass through a 1 mm sieve.
[0043] In certain embodiments, the diol component comprises: (i) from about 32 to about 42 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues, and (ii) from about 68 to about 58 mole % of ethylene glycol residues; or (i) from about 34 to about 40 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues, and (ii) from about 66 to about 60 mole % of ethylene glycol residues; or (i) greater than 34 to about 40 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues, and (ii) less than 66 to about 60 mole % of ethylene glycol residues. % ethylene glycol residues; or (i) 34.2 to about 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues, and (ii) 65.8 to about 60 mole % ethylene glycol residues; or (i) about 35 to about 39 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues, and (ii) about 65 to about 61 mole % ethylene glycol residues; or (i) about 36 to about 37 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; and (ii) about 64 to about 63 mole % ethylene glycol residues.
[0044] In one embodiment, the copolyester comprises:
[0045] (a) a dicarboxylic acid component comprising:
[0046] (i) from about 90 to about 100 mole percent of terephthalic acid residues;
[0047] (ii) from about 0 to about 10 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and
[0048] (b) a diol component comprising:
[0049] (i) from about 30 to about 42 mole percent of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues; and
[0050] (ii) from about 70 to about 58 mole percent of ethylene glycol residues, and
[0051] (iii) less than about 5 mole % or less than 2 mole % of any other modifying glycol;
[0052] wherein the total mole % of the dicarboxylic acid component is 100 mole %, and
[0053] wherein the total mole % of the diol component is 100 mole %; and
[0054] The polyester has an inherent viscosity of 0.50 to 0.70 dL / g as measured at a concentration of 0.25 g / 50 ml in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25°C.
[0055] In an embodiment, the copolyester has at least one of the following properties selected from the group consisting of: a Tg of about 100°C to about 110°C, as measured by a TA2100 thermal analyzer at a scan rate of 20°C / min; a flexural modulus at 23°C equal to or greater than 2000 MPa (about 290,000 psi) or greater than 2200 MPa (319,000 psi), as defined by ASTM D790; a notched Izod impact strength of about 30 J / m (0.56 ft-lb / in) to about 80 J / m (1.50 ft-lb / in), as measured according to ASTM D256 using a 1 / 8 inch thick bar at 23°C with a 10 mil notch; and an intrinsic viscosity loss of less than 5% after being held at a temperature of 293°C (560°F) for 2 minutes. In one embodiment, the polyester composition has an L* color value of 90 or greater or greater than 90 as determined by the L*a*b* color system measured according to ASTM D 6290-98 and ASTM E308-99 on polymer particles ground to pass through a 1 mm screen.
[0056] In one embodiment, the copolyester comprises: a diol component having at least 30 mole percent TMCD residues (based on the diol); and a catalyst / stabilizer component comprising: (i) titanium atoms in the range of 10-60 ppm based on the weight of the polymer, (ii) manganese atoms in the range of 10-100 ppm based on the weight of the polymer, and (iii) phosphorus atoms in the range of 10-200 ppm based on the weight of the polymer. In one embodiment, the 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues are a mixture comprising more than 50 mole percent cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol residues and less than 50 mole percent trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol residues.
[0057] In an embodiment, the diol component of the copolyester includes, but is not limited to, at least one of the following combinations of ranges: about 30 to about 42 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 58 to 70 mole percent ethylene glycol; about 32 to about 42 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 58 to 68 mole percent ethylene glycol; about 32 to about 36 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 64 to 68 mole percent ethylene glycol; about 33 to about 41 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 59 to 67 mole percent ethylene glycol; about 34 to about 40 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 60 to 66 mole percent ethylene glycol; greater than 34 to about 40 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to less than 66 mole percent ethylene glycol; 34.2 to 40 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 60 to 65.8 mole percent ethylene glycol; about 35 to about 39 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 61 to 65 mole percent ethylene glycol; about 35 to about 38 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 62 to 65 mole percent ethylene glycol; or about 36 to about 37 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol and about 63 to 64 mole percent ethylene glycol.
[0058] In certain embodiments, the polyester may exhibit at least one of the following intrinsic viscosities as measured at a concentration of 0.25 g / 50 ml in 60 / 40 (weight / weight) phenol / tetrachloroethane at 25° C.: 0.50 to 0.70 dL / g; 0.55 to 0.65 dL / g; 0.56 to 0.64 dL / g; 0.56 to 0.63 dL / g; 0.56 to 0.62 dL / g; 0.56 to 0.61 dL / g; 0.57 to 0.64 dL / g; 0.58 to 0.64 dL / g; 0.57 to 0.63 dL / g; 0.57 to 0.62 dL / g; 0.57 to 0.61 dL / g; 0.58 to 0.60 dL / g or about 0.59 dL / g.
[0059] In embodiments, the copolyester comprises 0 to 10 mole percent CHDM residues. In certain embodiments, the copolyester may contain less than 10 mole percent, or less than 5 mole percent, or less than 4 mole percent, or less than 3 mole percent, or less than 2 mole percent, or less than 1 mole percent CHDM residues, or no CHDM residues.
[0060] In embodiments, the polyesters may be prepared from monomers that do not contain 1,3-propanediol or 1,4-butanediol, alone or in combination. In other aspects, 1,3-propanediol or 1,4-butanediol, alone or in combination, may be used to prepare the polyesters useful in the present invention.
[0061] In embodiments, the mole percent of cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol in certain polyesters is greater than 50 mole percent, or greater than 55 mole percent of cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol, or greater than 70 mole percent of cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol; wherein the total mole percent of cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol and trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol equals a total of 100 mole percent.
[0062] In embodiments, the mole percent of isomers of 2,2,4,4-tetramethyl-1,3-cyclobutanediol in certain polyesters is from 30 to 70 mole percent cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol or from 30 to 70 mole percent trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol, or from 40 to 60 mole percent cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol or from 40 to 60 mole percent trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol, wherein the total mole percent of cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol and trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol equals a total of 100 mole percent.
[0063] In certain embodiments, the polyester can be amorphous or semi-crystalline. In one aspect, certain polyesters can have a relatively low degree of crystallinity. Thus, certain polyesters can have a substantially amorphous morphology, meaning that the polyester comprises substantially disordered polymer regions.
[0064] In embodiments, the polyesters and / or polyester compositions may have a unique combination of two or more physical properties, such as high impact strength, moderate to high glass transition temperature, chemical resistance, hydrolytic stability, toughness, low tough-brittle transition temperature, good color and clarity, low density, long crystallization half-life, and good processability, making them easy to shape into articles. In some embodiments, the polyesters may have a unique combination of properties such as good impact strength, heat resistance, chemical resistance, density, and / or a combination of properties such as good impact strength, heat resistance, and processability, and / or a combination of two or more of the properties.
[0065] In embodiments, polyesters may be prepared from dicarboxylic acids and diols that react in substantially equal proportions and are incorporated into polyester polymers as their respective residues. Thus, polyesters may contain substantially equal molar proportions of acid residues (100 mole %) and diol (and / or polyfunctional hydroxy compound) residues (100 mole %) such that the total moles of repeating units are equal to 100 mole %. Thus, the mole percentages provided in the present disclosure may be based on the total moles of acid residues, the total moles of diol residues, or the total moles of repeating units. For example, a polyester containing 30 mole % of isophthalic acid based on total acid residues means that the polyester contains 30 mole % of isophthalic acid residues in a total of 100 mole % of acid residues. Thus, there are 30 moles of isophthalic acid residues in every 100 moles of acid residues. In another example, a polyester containing 30 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on total diol residues means that the polyester contains 30 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues out of a total of 100 mole % of diol residues. Thus, for every 100 moles of diol residues, there are 30 moles of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues.
[0066] In an embodiment, the Tg of the polyester may be at least one of the following ranges: 100°C to 200°C; 100°C to 190°C; 100°C to 180°C; 100°C to 170°C; 100°C to 160°C; 100°C to 155°C; 100°C to 150°C; 100°C to 145°C; 100°C to 140°C; 100°C to 138°C; 100°C to 135°C; 100°C to 130°C; 100°C to 125°C; 100°C to 120°C; 100°C to 115°C; 100°C to 110°C; 105°C to 200°C; 105°C to 190°C; 105°C to 180°C; 105°C to 170°C; 105°C to 160°C; 105°C to 155°C; 10 5℃ to 150℃; 105℃ to 145℃; 105℃ to 140℃; 105℃ to 138℃; 105℃ to 135℃; 105℃ to 130℃; 105℃ to 125℃; 105℃ to 120℃; 105℃ to 115℃; 105℃ to 110℃ greater than 105℃ to 125℃; greater than 105℃ to 120℃; greater than 105℃ to 115℃; greater than 105℃ to 110℃; 110℃ to 200℃; 110℃ to 190℃; 110℃ to 180℃; 110℃ to 170℃; 110℃ to 160℃; 110℃ to 155℃; 110℃ to 150℃; 110℃ to 145℃; 110℃ to 140℃; 110℃ to 138℃; 110 ℃ to 135℃; 110℃ to 130℃; 110℃ to 125℃; 110℃ to 120℃; 110℃ to 115℃; 115℃ to 200℃; 115℃ to 190℃; 115℃ to 180℃; 115℃ to 170℃; 115℃ to 160℃; 115℃ to 155℃; 115℃ to 150℃; 115℃ to 14 5℃; 115℃ to 140℃; 115℃ to 138℃; 115℃ to 135℃; 110℃ to 130℃; 115℃ to 125℃; 115℃ to 120℃; 120℃ to 200℃; 120℃ to 190℃; 120℃ to 180℃; 120℃ to 170℃; 120℃ to 160℃; 120℃ to 155℃; 1 20℃ to 150℃; 120℃ to 145℃; 120℃ to 140℃; 120℃ to 138℃; 120℃ to 135℃; 120℃ to 130℃; 125℃ to 200℃; 125℃ to 190℃; 125℃ to 180℃; 125℃ to 170℃; 125℃ to 160℃; 125℃ to 155℃; 125℃ to 150℃; 125℃ to 145℃; 125℃ to 140℃; 125℃ to 138℃; 125℃ to 135℃; 127℃ to 200℃; 127℃ to 190℃; 127℃ to 180℃; 127℃ to 170℃; 127℃ to 160℃; 127℃ to 150℃; 127℃ to 145℃; 127℃ to 140℃;127℃ to 138℃; 127℃ to 135℃; 130℃ to 200℃; 130℃ to 190℃; 130℃ to 180℃; 130℃ to 170℃; 130℃ to 160℃; 130℃ to 155℃; 130℃ to 150℃; 130℃ to 145℃; 130℃ to 140℃; 130℃ to 138℃; 130℃ to 135℃; 135℃ to 200℃; 135℃ to 190℃; 135℃ to 180℃; 135℃ to 170℃; 135℃ to 160℃; 135℃ to 155℃; 135℃ to 150℃; 135℃ to 145℃; 135℃ to 140℃; 140℃ to 200℃; 1 40°C to 190°C; 140°C to 180°C; 140°C to 170°C; 140°C to 160°C; 140°C to 155°C; 140°C to 150°C; 140°C to 145°C; 148°C to 200°C; 148°C to 190°C; 148°C to 180°C; 148°C to 170°C; 148°C to 160°C; 148°C to 155°C; 148°C to 150°C; 150°C to 200°C; 150°C to 190°C; 150°C to 180°C; 150°C to 170°C; 150°C to 160°C; 155°C to 190°C; 155°C to 180°C; 155°C to 170°C; and 155°C to 165°C.
[0067] For certain embodiments, the polyester may exhibit at least one of the following intrinsic viscosities as measured at a concentration of 0.5 g / 100 ml in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25° C.: 0.10 to 1.2 dL / g; 0.10 to 1.1 dL / g; 0.10 to 1 dL / g; 0.10 to less than 1 dL / g; 0.10 to 0.98 dL / g; 0.10 to 0.95 dL / g; 0.10 to 0.90 dL / g; 0.10 to 0.85 dL / g; 0.10 to 0.80 dL / g; 0.10 to 0.75 dL / g; 0.10 to less than 0.75 dL / g; 0.10 to 0.72 dL / g; 0.10 to 0.70 dL / g g; 0.10 to less than 0.70 dL / g; 0.10 to 0.68 dL / g; 0.10 to less than 0.68 dL / g; 0.10 to 0.65 dL / g; 0.20 to 1.2 dL / g; 0.20 to 1.1 dL / g; 0.20 to 1 dL / g; 0.20 to less than 1 dL / g; 0.20 to 0.98 dL / g; 0.20 to 0.95 dL / g; 0.20 to 0.90 dL / g; 0.20 to 0.85 dL / g; 0.20 to 0.80 dL / g; 0.20 to 0.75 dL / g; 0.20 to less than 0.75 dL / g; 0.20 to 0.72 dL / g; 0.20 to 0.70 dL / g; 0.20 to less than 0. 70 dL / g; 0.20 to 0.68 dL / g; 0.20 to less than 0.68 dL / g; 0.20 to 0.65 dL / g; 0.35 to 1.2 dL / g; 0.35 to 1.1 dL / g; 0.35 to 1 dL / g; 0.35 to less than 1 dL / g; 0.35 to 0.98 dL / g; 0.35 to 0.95 dL / g; 0.35 to 0.90 dL / g; 0.35 to 0.85 dL / g; 0.35 to 0.80 dL / g; 0.35 to 0.75 dL / g; 0.35 to less than 0.75 dL / g; 0.35 to 0.72 dL / g; 0.35 to 0.70 dL / g; 0.35 to less than 0.70 dL / g; 0.35 to 0.68 dL / g; 0.35 to less than 0.68 dL / g; 0.35 to 0.65 dL / g; 0.40 to 1.2 dL / g; 0.40 to 1.1 dL / g; 0.40 to 1 dL / g; 0.40 to less than 1 dL / g; 0.40 to 0.98 dL / g; 0.40 to 0.95 dL / g; 0.40 to 0. 90dL / g; 0.40 to 0.85dL / g; 0.40 to 0.80dL / g; 0.40 to 0.75dL / g; 0.40 to less than 0.75dL / g; 0.40 to 0.72dL / g; 0.40 to 0.70dL / g; 0.40 to less than 0.70dL / g; 0.40 to 0.68dL / g; 0.40 to less than 0.68 dL / g; 0.40 to 0.65 dL / g; greater than 0.42 to 1.2 dL / g; greater than 0.42 to 1.1 dL / g; greater than 0.42 to 1 dL / g; greater than 0.42 to less than 1 dL / g; greater than 0.42 to 0.98 dL / g; greater than 0.42 to 0.95 dL / g; greater than 0.42 to 0.90 dL / g; greater than 0.42 to 0. 85 dL / g; greater than 0.42 to 0.80 dL / g; greater than 0.42 to 0.75 dL / g; greater than 0.42 to less than 0.75 dL / g; greater than 0.42 to 0.72 dL / g; greater than 0.42 to less than 0.70 dL / g; greater than 0.42 to 0.68 dL / g; greater than 0.42 to less than 0.68 dL / g; and greater than 0.42 to 0.65 dL / g.
[0068] For certain embodiments, the polyester may exhibit at least one of the following intrinsic viscosities as measured at a concentration of 0.5 g / 100 ml in 60 / 40 (weight / weight) phenol / tetrachloroethane at 25° C.: 0.45 to 1.2 dL / g; 0.45 to 1.1 dL / g; 0.45 to 1 dL / g; 0.45 to 0.98 dL / g; 0.45 to 0.95 dL / g; 0.45 to 0.90 dL / g; 0.45 to 0.85 dL / g; 0.45 to 0.80 dL / g; 0.45 to 0.75 dL / g; 0.45 to less than 0.75 dL / g; 0.45 to 0.72 dL / g; 0.45 to 0.70 dL / g; 0.45 to less than 0.70 dL / g. L / g; 0.45 to 0.68 dL / g; 0.45 to less than 0.68 dL / g; 0.45 to 0.65 dL / g; 0.50 to 1.2 dL / g; 0.50 to 1.1 dL / g; 0.50 to 1 dL / g; 0.50 to less than 1 dL / g; 0.50 to 0.98 dL / g; 0.50 to 0.95 dL / g ; 0.50 to 0.90 dL / g; 0.50 to 0.85 dL / g; 0.50 to 0.80 dL / g; 0.50 to 0.75 dL / g; 0.50 to less than 0.75 dL / g; 0.50 to 0.72 dL / g; 0.50 to 0.70 dL / g; 0.50 to less than 0.70 dL / g; 0.50 to 0.6 8dL / g; 0.50 to less than 0.68dL / g; 0.50 to 0.65dL / g; 0.55 to 1.2dL / g; 0.55 to 1.1dL / g; 0.55 to 1dL / g; 0.55 to less than 1dL / g; 0.55 to 0.98dL / g; 0.55 to 0.95dL / g; 0.55 to 0.90dL / g; 0.55 to 0.85dL / g; 0.55 to 0.80dL / g; 0.55 to 0.75dn / g; 0.55 to less than 0.75dL / g; 0.55 to 0.72dL / g; 0.55 to 0.70dL / g; 0.55 to less than 0.70dL / g; 0.55 to 0.68dL / g; 0.55 to less than 0.68 dL / g; 0.55 to 0.65 dL / g; 0.58 to 1.2 dL / g; 0.58 to 1.1 dL / g; 0.58 to 1 dL / g; 0.58 to less than 1 dL / g; 0.58 to 0.98 dL / g; 0.58 to 0.95 dL / g; 0.58 to 0.90 dL / g; 0.58 to 0.85 dL / g; 0.58 to 0.80 dL / g; 0.58 to 0.75 dL / g; 0.58 to less than 0.75 dL / g; 0.58 to 0.72 dL / g; 0.58 to 0.70 dL / g; 0.58 to less than 0.70 dL / g; 0.58 to 0.68 dL / g; 0.58 to less than 0.68 dL / g; 0.58 to 0.65 dL / g; 0.60 to 1.2 dL / g; 0.60 to 1.1 dL / g; 0.60 to 1 dL / g; 0.60 to less than 1 dL / g; 0.60 to 0.98 dL / g; 0.60 to 0.95 dL / g; 0.60 to 0.90 dL / g; 0.60 to 0.85 dL / g; 0.60 to 0.80 dL / g; 0.60 to 0.75 dL / g; 0.60 to less than 0.75 dL / g; 0.60 to 0.72 dL / g; 0.60 to 0.70 dL / g; 0.60 to less than 0.70 dL / g; 0.60 to 0.68 dL / g; 0.6 0 to less than 0.68 dL / g; 0.60 to 0.65 dL / g; 0.65 to 1.2 dL / g; 0.65 to 1.1 dL / g; 0.65 to 1 dL / g; 0.65 to less than 1 dL / g; 0.65 to 0.98 dL / g; 0.65 to 0.95 dL / g; 0.65 to 0.90 dL / g; 0.65 to 0.85 dL / g; 0.65 to 0.80 dL / g; 0.65 to 0.75 dL / g; 0.65 to less than 0.75 dL / g; 0.65 to 0.72 dL / g; 0.65 to 0.70 dL / g; 0.65 to less than 0.70 dL / g; 0.6 8 to 1.2 dL / g; 0.68 to 1.1 dL / g; 0.68 to 1 dL / g; 0.68 to less than 1 dL / g; 0.68 to 0.98 dL / g; 0.68 to 0.95 dL / g; 0.68 to 0.90 dL / g; 0.68 to 0.85 dL / g; 0.68 to 0.80 dL / g; 0.68 to 0.75 dL / g; 0.68 to less than 0.75 dL / g; 0.68 to 0.72 dL / g; greater than 0.76 dug to 1.2 dL / g; greater than 0.76 dL / g to 1.1 dL / g; greater than 0.76 dL / g to 1 dL / g; greater than 0.76 dL / g / g to less than 1dL / g; greater than 0.76dL / g to 0.98dL / g; greater than 0.76dL / g to 0.95dL / g; greater than 0.76dL / g to 0.90dL / g; greater than 0.80dL / g to 1.2dL / g; greater than 0.80dL / g to 1.1dL / g; greater than 0.80dL / g to 1dL / g; greater than 0.80dL / g to less than 1dL / g; greater than 0.80dL / g to 1.2dL / g; greater than 0.80dL / g to 0.98dL / g; greater than 0.80dL / g to 0.95dL / g; greater than 0.80dL / g to 0.90dL / g. .
[0069] In certain embodiments, unless otherwise stated, it is contemplated that the polyester composition may have at least one of the intrinsic viscosity ranges described herein and at least one of the monomer ranges for the composition described herein. Unless otherwise stated, it is also contemplated that the polyester composition may have at least one of the Tg ranges described herein and at least one of the monomer ranges for the composition described herein. Unless otherwise stated, it is also contemplated that the polyester composition may have at least one of the Tg ranges described herein, at least one of the intrinsic viscosity ranges described herein, and at least one of the monomer ranges for the composition described herein.
[0070] In embodiments, the molar ratio of cis / trans 2,2,4,4-tetramethyl-1,3-cyclobutanediol may vary depending on the respective pure forms or mixtures thereof. In certain embodiments, the mole percentage of cis and / or trans 2,2,4,4,-tetramethyl-1,3-cyclobutanediol is greater than 50 mole % cis and less than 50 mole % trans; or greater than 55 mole % cis and less than 45 mole % trans; or 30 to 70 mole % cis and 70 to 30% trans; or 40 to 60 mole % cis and 60 to 40 mole % trans; or 50 to 70 mole % trans and 50 to 30% cis or 50 to 70 mole % cis and 50 to 30% trans; or 60 to 70 mole % cis and 30 to 40 mole % trans; or greater than 70 mole % cis and less than 30 mole % trans; wherein the sum of the mole percentages of cis and trans-2,2,4,4-tetramethyl-1,3-cyclobutanediol is equal to 100 mole %. The molar ratio of cis / trans 1,4-cyclohexanedimethanol may vary within the range of 50 / 50 to 0 / 100, such as between 40 / 60 and 20 / 80.
[0071] In certain embodiments, terephthalic acid or its ester (such as dimethyl terephthalate) or a mixture of terephthalic acid and its ester constitutes most or all of the dicarboxylic acid component for forming polyester. In certain embodiments, terephthalic acid residues may constitute a part or all of the dicarboxylic acid component for forming polyester, and the concentration of terephthalic acid residues is at least 70 mol%, such as at least 80 mol%, at least 90 mol%, at least 95 mol%, at least 99 mol% or 100 mol%. In certain embodiments, a larger amount of terephthalic acid can be used to produce a polyester with higher impact strength. In one embodiment, dimethyl terephthalate is a part or all of the dicarboxylic acid component for preparing polyesters that can be used in the present invention. For the purpose of this disclosure, the reference to the residues of "terephthalic acid" and "dimethyl terephthalate" can be used interchangeably herein. For example, the reference to the polymer residues of terephthalic acid (TPA) also includes the polymer residues derived from dimethyl terephthalate (DMT). In all embodiments, a range of 70 to 100 mole %; or 80 to 100 mole %; or 90 to 100 mole %; or 99 to 100 mole %; or 100 mole % of terephthalic acid and / or dimethyl terephthalate and / or mixtures thereof may be used.
[0072] In addition to terephthalic acid, in certain embodiments, the dicarboxylic acid component of polyester may also include up to 30 mol %, up to 20 mol %, up to 10 mol %, up to 5 mol % or up to 1 mol % of one or more modified aromatic dicarboxylic acids. Another embodiment contains 0 mol % of modified aromatic dicarboxylic acids. Therefore, if present, it is expected that the starting value of the range of the amount of one or more modified aromatic dicarboxylic acids may be any one of these front end values, including, for example, 0.01 to 30 mol %, 0.01 to 20 mol %, 0.01 to 10 mol %, 0.01 to 5 mol % and 0.01 to 1 mol %. In one embodiment, the modified aromatic dicarboxylic acids that can be used include but are not limited to those with up to 20 carbon atoms, and may be linear, para-oriented or symmetrical. Examples of modified aromatic dicarboxylic acids that can be used include, but are not limited to, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, and trans-4,4'-stilbene dicarboxylic acid and their esters. In one embodiment, the modified aromatic dicarboxylic acid is isophthalic acid.
[0073] In embodiments, the carboxylic acid component of polyester can be further modified with up to 10 mol %, for example up to 5 mol % or up to 1 mol % of one or more aliphatic dicarboxylic acids containing 2-16 carbon atoms such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and dodecanedioic acid dicarboxylic acid. Some embodiments can also include 0.01 mol % or more, such as 0.1 mol % or more, 1 mol % or more, 5 mol % or more or 10 mol % or more of one or more modified aliphatic dicarboxylic acids. Another embodiment contains 0 mol % of modified aliphatic dicarboxylic acids. Therefore, if present, it is expected that the starting value of the range of the amount of one or more modified aliphatic dicarboxylic acids can be any one of these front end values, including for example 0.01 to 10 mol % and 0.1 to 10 mol %. The total mole % of dicarboxylic acid component is 100 mol %.
[0074] Can use terephthalic acid ester and other modified dicarboxylic acids or their corresponding ester and / or salt to replace dicarboxylic acid.Suitable example of dicarboxylic acid ester includes but not limited to dimethyl ester, diethyl ester, dipropyl ester, diisopropyl ester, dibutyl ester and diphenyl ester.In one embodiment, ester is selected from at least one of following: methyl ester, ethyl ester, propyl ester, isopropyl ester and phenyl ester.
[0075] In embodiments of polyesters containing CHDM, the 1,4-cyclohexanedimethanol may be cis, trans, or a mixture thereof, such as in a cis / trans ratio of 60:40 to 40:60.
[0076] In embodiments, the polyesters may be linear or branched. In embodiments, the polycarbonates (if included) may also be linear or branched. In certain embodiments, branching monomers or branching agents may be added before and / or during and / or after polymerization of the polycarbonate.
[0077] Examples of branching monomers include, but are not limited to, polyfunctional acids or polyfunctional alcohols such as trimellitic acid, trimellitic anhydride, pyromellitic dianhydride, trimethylolpropane, glycerol, pentaerythritol, citric acid, tartaric acid, 3-hydroxyglutaric acid, and the like. In one embodiment, the branching monomer residues may comprise 0.1 to 0.7 mole percent of one or more residues selected from at least one of trimellitic anhydride, pyromellitic dianhydride, glycerol, sorbitol, 1,2,6-hexanetriol, pentaerythritol, trimethylolethane, and / or trimesic acid. The branching monomers may be added to the polyester reaction mixture or blended with the polyester in the form of a concentrate, such as described in U.S. Pat. Nos. 5,654,347 and 5,696,176, the disclosures of which regarding branching monomers are incorporated herein by reference.
[0078] The glass transition temperature (Tg) of the polyester can be measured using a TA DSC2920 from Thermal Analyst Instrument at a scanning rate of 20°C / min.
[0079] The long crystallization half-life at 170° C. (e.g., greater than 5 minutes) exhibited by certain polyesters can be beneficial for the production of certain injection molded, compression molded, and solution cast articles. The polyesters can be amorphous or semi-crystalline. In one aspect, certain polyesters can have a relatively low degree of crystallinity. Thus, certain polyesters can have a substantially amorphous morphology, meaning that the polyester comprises substantially disordered polymer regions.
[0080] In one embodiment, the "amorphous" polyester may have a crystallization half-time of greater than 5 minutes at 170°C, or greater than 10 minutes at 170°C, or greater than 50 minutes at 170°C, or greater than 100 minutes at 170°C. In one embodiment, the crystallization half-time is greater than 1,000 minutes at 170°C. In another embodiment of the present invention, the crystallization half-time of the polyester useful in the present invention is greater than 10,000 minutes at 170°C. The crystallization half-time of the polyester as used herein can be measured using methods well known to those skilled in the art. For example, the crystallization half-time of the polyester t 1 / 2 It can be determined by measuring the light transmittance of a sample over time on a temperature-controlled hot stage using a laser and a photodetector. This measurement can be performed by exposing the polymer to a temperature T max This is done by heating the sample to a temperature of 100 °C and then cooling it to the desired temperature. The sample can then be held at the desired temperature by a hot stage while transmittance measurements are taken over time. Initially, the sample may be visually transparent with high light transmittance, but becomes opaque as the sample crystallizes. The crystallization half-life is the time it takes for the light transmittance to be halfway between the initial transmittance and the final transmittance. max Defined as the temperature required to melt the crystalline domains of the sample (if any). The sample can be heated to T max , in order to condition the samples before crystallization half-time measurements. The absolute T for each composition max The temperature is different. For example, PCT may have to be heated to a temperature above 290°C to melt the crystalline domains.
[0081] In embodiments, certain polyesters are visually transparent. The term "visually transparent" is defined herein as being significantly free of turbidity, haziness, and / or turbidity when visually inspected. In one embodiment, when the polyester is blended with a polycarbonate (including bisphenol A polycarbonate), the blend may be visually transparent. In embodiments, the polyester may have one or more properties described herein. In embodiments, the polyester may have a yellowness index (ASTM D-1925) of less than 50, such as less than 20.
[0082] The copolyester portion of the polymer composition of the present invention can be prepared by methods known in the literature, such as, for example, by methods in homogeneous solution, by transesterification methods in the melt, and by two-phase interface methods. Suitable methods include, but are not limited to, the step of reacting one or more dicarboxylic acids with one or more diols at a temperature of 100° C. to 315° C., at a pressure of 0.1 to 760 min Hg, for a time sufficient to form polyesters. For methods of producing polyesters, see U.S. Pat. No. 3,772,405, the disclosure of which is hereby incorporated by reference herein.
[0083] Generally, the copolyester can be prepared by a process comprising: (I) heating a mixture comprising monomers of any polyester useful in the present invention at a temperature of 150°C to 240°C for a time sufficient to produce an initial polyester in the presence of a catalyst; (II) heating the initial polyester of step (I) at a temperature of 240°C to 320°C for 1 to 4 hours; and (III) removing any unreacted diol.
[0084] Catalysts suitable for use in the process include, but are not limited to, organozinc or tin compounds. The use of catalysts of this type is well known in the art. Examples of catalysts that can be used in the present invention include, but are not limited to, zinc acetate, butyltin tri-2-ethylhexanoate, dibutyltin diacetate, and dibutyltin oxide. Other catalysts may include, but are not limited to, those based on titanium, zinc, manganese, lithium, germanium, and cobalt. The amount of the catalyst may be based on the catalyst metal and based on the weight of the final polymer in the range of 10 ppm to 20,000 ppm or 10 to 10,000 ppm, or 10 to 5000 ppm, or 10 to 1000 ppm, or 10 to 500 ppm, or 10 to 300 ppm, or 10 to 250. The process may be performed in an intermittent or continuous process.
[0085] Typically, step (I) may be performed until 50 weight percent or more of the 2,2,4,4-tetramethyl-1,3-cyclobutanediol has reacted. Step (I) may be performed at a pressure ranging from atmospheric pressure to 100 psig. The term "reaction product" used in conjunction with any catalyst useful in the present invention refers to any product of a polycondensation or esterification reaction using the catalyst and any monomer used to prepare polyesters, as well as the product of a polycondensation or esterification reaction between the catalyst and any other type of additive.
[0086] Typically, step (II) and step (III) can be performed simultaneously. These steps can be performed by methods known in the art, such as by placing the reaction mixture under a pressure ranging from 0.002 psig to below atmospheric pressure, or by blowing hot nitrogen over the mixture.
[0087] In an embodiment, the polyester composition can be a polymer blend, wherein the blend comprises: (a) 5 to 95 weight percent of at least one polyester described herein; and (b) 5 to 95 weight percent of at least one polymer component. Suitable examples of polymer components include, but are not limited to, nylon, polyesters other than those described herein, polyamides (such as nylon 9000 from DuPont), ... ); polystyrene, polystyrene copolymers, styrene acrylonitrile copolymers, acrylonitrile butadiene styrene copolymers, poly(methyl methacrylate), acrylic acid copolymers, poly(ether-imides) such as ULTEM TM Resin (poly(ether-imide) from SABIC); polyphenylene ether such as poly(2,6-dimethylphenylene ether) or poly(phenylene ether) / polystyrene blends such as NORYL TM resin (a blend of poly(2,6-dimethylphenylene oxide) and polystyrene resin from SABIC); polyphenylene sulfide; polyphenylene sulfide / sulfone; poly(ester-carbonate); polycarbonates such as (polycarbonate from SABIC); polysulfone; polysulfone ether; and poly(ether-ketone) of aromatic dihydroxy compounds; or any other mixture of the foregoing polymers. The blends can be prepared by conventional processing techniques known in the art, such as melt blending or solution blending. In one embodiment, polycarbonate is not present in the polyester composition. If polycarbonate is used in a blend useful in the polyester composition of the present invention, the blend can be visually transparent. However, the polyester composition useful in the present invention also contemplates the exclusion of polycarbonate as well as the inclusion of polycarbonate.
[0088] In addition to additives and optional impact modifiers (as discussed herein), the polyester compositions and polymer blend compositions may also contain additional additives selected from antioxidants, heat stabilizers, mold release agents, antistatic agents, brighteners, colorants, flow aids, processing aids, plasticizers, anti-fog additives, minerals, UV stabilizers, lubricants, chain extenders, nucleating agents, reinforcing fillers, other fillers, glass fibers, carbon fibers, flame retardants, dyes, pigments, colorants, additional resins, and combinations thereof. In certain embodiments, the polyester compositions and polymer blend compositions may also contain from 0.01% to 25% of common additives such as colorants, dyes, mold release agents, flame retardants, plasticizers, nucleating agents, stabilizers (including but not limited to UV stabilizers, heat stabilizers and / or reaction products thereof), and fillers, based on the weight of the overall composition. For example, UV additives may be incorporated into an article (e.g., an ophthalmic product) by addition to the body or hardcoat.
[0089] In some embodiments, during the preparation of the polyesters useful in the present invention, certain agents that color the polymers may be added to the melt, including toners or dyes. In one embodiment, a bluing toner is added to the melt to adjust the b* of the resulting polyester polymer melt phase product. Such bluing agents include blue inorganic and organic toners and / or dyes. In addition, red toners and / or dyes may also be used to adjust the a* color. In one embodiment, the polymers or polymer blends useful in the present invention and / or the polymer compositions of the present invention (with or without toners) may have color values L*, a*, and b* that can be measured using a Hunter Lab Ultrascan Spectra Colorimeter manufactured by Hunter Associates Lab Inc., Reston, Va. The color measurement results are the average of the values measured for pellets or powders of the polymer or plaques or other articles thereof that are injection molded or extruded. They are measured by the L*a*b* color system of CIE (International Commission on Illumination) (translation), where L* represents the photometric coordinate, a* represents the red / green coordinate, and b* represents the yellow / blue coordinate. Organic toners, for example, blue and red organic toners, such as those described in U.S. Pat. Nos. 5,372,864 and 5,384,377, which are incorporated by reference in their entirety, can be used. The organic toners can be fed as a premixed composition. The premixed composition can be a neat blend of the red and blue compounds, or the composition can be pre-dissolved or slurried in one of the polyester raw materials (e.g., ethylene glycol).
[0090] The total amount of toner components added may depend on the amount of inherent yellow in the base polyester and the efficacy of the toner. In one embodiment, a concentration of up to about 15 ppm of combined organic toner components and a minimum concentration of about 0.5 ppm may be used. In one embodiment, the total amount of bluing additive may be in the range of 0.5 to 10 ppm. In one embodiment, the toner may be added to the esterification zone or the polycondensation zone. Advantageously, the toner is added to the esterification zone or to the early stages of the polycondensation zone, such as to the prepolymerization reactor or to the extruder or calender during processing.
[0091] In an embodiment, the polyester may include at least one chain extender. Suitable chain extenders include, but are not limited to, multifunctional (including but not limited to difunctional) isocyanates, multifunctional epoxides (including, for example, epoxidized phenolic resins), and phenoxy resins. In certain embodiments, the chain extender may be added at the end of the polymerization process or after the polymerization process. If added after the polymerization process, the chain extender may be incorporated by compounding or by addition during a conversion process such as injection molding or extrusion. The amount of chain extender used may vary depending on the specific monomer composition used and the desired physical properties, but is typically 0.1 weight percent to 10 weight percent, such as 0.1 to 5 weight percent, based on the total weight of the polyester.
[0092] Heat stabilizers are compounds that stabilize polyesters during polyester manufacturing and / or post-polymerization processes, including but not limited to phosphorus compounds, including but not limited to phosphoric acid, phosphorous acid, phosphonic acid, phosphinic acid, phosphous acid, and various esters and salts thereof. Esters can be alkyl, branched alkyl, substituted alkyl, difunctional alkyl, alkyl ether, aryl, and substituted aryl. In one embodiment, the number of ester groups present in a particular phosphorus compound can vary from zero to a maximum value that can be allowed based on the number of hydroxyl groups present on the heat stabilizer used. The term "heat stabilizer" is intended to include its reaction products. The term "reaction product" used in conjunction with the heat stabilizer of the present invention refers to any product of a polycondensation or esterification reaction between a heat stabilizer and any monomer used to prepare polyester, as well as a product of a polycondensation or esterification reaction between a catalyst and any other type of additive. In an embodiment, these may be present in a polyester composition.
[0093] In embodiments, reinforcing materials can be used for polyester compositions. Reinforcing materials can include, but are not limited to, carbon filaments, silicates, mica, clay, talc, titanium dioxide, wollastonite, glass flakes, glass beads and fibers and polymer fibers and combinations thereof. In one embodiment, reinforcing materials are glass, such as fiberglass filaments, a mixture of glass and talc, a mixture of glass and mica, and a mixture of glass and polymer fibers.
[0094] In another embodiment, the present invention also relates to articles comprising any of the polyesters and blends described herein. Extruded, calendered and / or molded articles include, but are not limited to, injection molded articles, extruded articles, cast extruded articles, profile extruded articles, melt-spun articles, thermoformed articles, extrusion molded articles, injection blow molded articles, injection stretch blow molded articles, extrusion blow molded articles, and extrusion stretch blow molded articles. These articles may include, but are not limited to, films, bottles (including, but not limited to, baby bottles), containers, sheets, and / or fibers.
[0095] In an embodiment, the article may be intended for use in applications where the article (or a component thereof) has surface-to-surface contact (with another article or component) where movement is expected to occur at the surface contact, for example, the surfaces are expected to slide against each other. Such applications may include articles, parts or components that are releasably connected to each other (e.g., connected by friction). Examples of such applications may include durable articles or toys (e.g., puzzle toys) having articles, parts or components that interact when used as described above. In an embodiment, the polyester composition or an article made therefrom may be an application currently made of ABS plastic (e.g., a common toy, electronic product, or medical device). Other examples of articles may include transparent or opaque food contact applications, for example, food containers, lids, bottles (including sports bottles and lids) and fasteners and hinges thereof, including fastener and hinge integrated components and / or assemblies.
[0096] The copolyesters and / or polyester blend compositions of the present invention can be used to form fibers, films, molded articles, containers and sheets. Methods of molding polyester into fibers, films, molded articles, containers and sheets are well known in the art. Examples of possible molded articles include, but are not limited to, medical devices (such as dialysis equipment), medical packaging, health care products, commercial food service products (such as food trays, cups and storage boxes), baby bottles, food processors, blenders and mixing bowls, tableware, water bottles, fresh-keeping box trays, toys, washing machine fronts and vacuum cleaner parts, and lids, locks and hinges attached to the above items.
[0097] In another embodiment, the present invention is also directed to articles comprising films and / or sheets comprising the polyester compositions described herein.
[0098] Films and / or sheets useful for the present invention may have any thickness that will be apparent to one of ordinary skill in the art. In one embodiment, the film of the present invention has a thickness of no more than 40 mils. In one embodiment, the film of the present invention has a thickness of no more than 35 mils. In one embodiment, the film of the present invention has a thickness of no more than 30 mils. In one embodiment, the film of the present invention has a thickness of no more than 25 mils. In one embodiment, the film of the present invention has a thickness of no more than 20 mils.
[0099] In an embodiment, the (friction) additive may be selected from a wide variety of waxes and silicones. Waxes that can be used in the polymer compositions of the present invention may include known higher alkanes and lipids, which are lipophilic, ductile solids at room temperature (i.e., 23°C). Natural waxes are found in plants and animals, and are also found in petroleum products. In one embodiment, the wax is a mixture of saturated alkanes, naphthenes, and alkyl- and cycloalkane-substituted aromatic compounds. In another embodiment, the wax may be a montan wax extracted from certain coal and lignite sources. In another embodiment, the wax may be a polyolefin or polyethylene wax (polyalkylene wax). Naturally occurring waxes may include beeswax, primarily beeswax palmitate, cetyl palmitate, lanolin, carnauba wax. In another embodiment, the wax may be rice bran wax (RBW), for example, RBW derived from crude rice bran, such as RBW Vita Supplement (from Clariant).
[0100] In an embodiment, the siloxane may be a compound containing Si-O-Si bonds. Examples include compounds having the structures H(OSiH2)nOH and (OSiH2)n. In other embodiments, the siloxane may be an organosilicon or polysiloxane having the structure (-RSi-O-SiR-), where R is an organic group, such as an alkyl or aryl group. Examples of such polysiloxanes are polydimethylsiloxane or "PDMS" and polydiphenylsiloxane.
[0101] Commercially available examples of waxes and silicones may include Genioplast S, a pelletized silicone gum formulation from Wacker Chemie AG; Tegomer H-Si (e.g., H-Si 6441P) (polyester-modified silicone), Tegomer V-Si (e.g., V-Si 4042) (vinyl-terminated organic modified silicone (OMS)), Tegomer M-Si (e.g., M-Si 2650) (aryl-terminated OMS), Tegomer E-Si (e.g., E-Si 2330) (epoxy-terminated OMS) or Tegomer DA 800 (copolyester dispersion), all from Evonik Industries AG; MCR-E21 or ECMS-227 functionalized silicones from Gelest; Dowsil TMSi powder resin modifier or DowSil 4-7081 from Dow Chemical Company; Loxiol P or P861, polyol esters from Emery Oleochemicals GmbH; Modiper 1401, 4300 or 4400 (polyethylene-based (graft) copolymers) from Nippon Oil & Fat Corporation; AC Wax 307, 316 or 325 (polyethylene polymer powder) from Honeywell; Licowax OP, E, PED191, 371FP or WE 40 from Clariant; Hystrene (fatty acid) from PMC Group; Licocare RBW101, 102, 106, 300, 330, 360 Vita and Ceridust 1060 and 1041 TP Vita from Clariant; repellent polymer PM-870 or FX 5911 (fluorochemical flakes) from 3M; and Incroslip or Incromax 100 (bio-based slip additives) from Croda. It should be noted that some of these additives can provide other functions to the copolyester resin in addition to friction modifiers. For example, Modiper 4300 and 4400 can also be used as impact modifiers.
[0102] The waxes and silicones used as component (b) above are generally present in an amount of about 0.1 to about 12 weight percent. In other embodiments, they are present in an amount of about 0.1 to about 10, or 1 to about 10 weight percent based on the total polyester composition. In an embodiment, component (b) additive comprises a wax and is present in an amount of 0.1 to 12 wt%, or 0.1 to 10 wt%, or 0.1 to 8 wt%, or 0.1 to 6 wt%, or 0.1 to 4 wt%, or 0.1 to 3 wt%, or 0.1 to 2 wt%, or 0.1 to 1.5 wt%, or 0.1 to 1.3 wt%, or 0.1 to 1.2 wt%, or 0.1 to 1.1 wt%, or 0.1 to 1.0 wt%, 0.2 to 4 wt%, or 0.2 to 3 wt%, or 0.2 to 2 wt%, or 0.2 to 1.5 wt%, or 0.2 to 1.3 wt%, or 0.2 to 1.2 wt%, or 0.2 to 1.1 wt%, or 0.2 to 1.0 wt%, or 0.3 to 4 wt%, or %, or 0.3 to 3 wt %, or 0.3 to 2 wt %, or 0.3 to 1.5 wt %, or 0.3 to 1.3 wt %, or 0.3 to 1.2 wt %, or 0.3 to 1.1 wt %, or 0.3 to 1.0 wt %, or 0.4 to 4 wt %, or 0.4 to 3 wt %, or 0.4 to 2 wt %, or 0.4 to 1.5 wt %, or 0.4 to 1.3 wt %, or 0.4 to 1.2 wt %, or 0.4 to 1.1 wt %, or 0.4 to 1.0 wt %, or 0.5 to 4 wt %, or 0.5 to 3 wt %, or 0.5 to 2 wt %, or 0.5 to 1.5 wt %, or 0.5 to 1.3 wt %, or 0.5 to 1.2 wt %, or 0.5 to 1.1 wt %, or 0.5 to 1.0 wt %.
[0103] In an embodiment, component (b) additive comprises siloxane and is present in an amount of 0.1 to 12 wt%, or 1 to 12 wt%, or 1 to 11 wt%, or 1 to 10 wt%, or 1 to 9 wt%, or 1 to 8 wt%, or 2 to 12 wt%, or 2 to 11 wt%, or 2 to 10 wt%, or 2 to 9 wt%, or 2 to 8 wt%, or 3 to 12 wt%, or 3 to 11 wt%, or 3 to 10 wt%, based on the total weight of the polyester composition. %, or 3 to 9 weight %, or 3 to 8 weight %, or 4 to 12 weight %, or 4 to 11 weight %, or 4 to 10 weight %, or 4 to 9 weight %, or 4 to 8 weight %, or 5 to 12 weight %, or 5 to 11 weight %, or 5 to 10 weight %, or 5 to 9 weight %, or 5 to 8 weight %, or 6 to 12 weight %, or 6 to 11 weight %, or 6 to 10 weight %, or 6 to 9 weight %, or 6 to 8 weight %.
[0104] About component (c) impact modifier, such compounds are usually elastomeric compounds or polymers, which are used to absorb or dissipate the kinetic energy of impact. A wide variety of known materials can be used for component (c). Various impact modifiers can be used to practice the present invention. Preferred impact modifiers are those that include at least one functional group capable of reacting with at least one end group of a macrocyclic polyester oligomer. Examples of suitable impact modifiers include, but are not limited to, various known graft copolymers, core-shell polymers, and block copolymers. These polymers may include at least one monomer selected from the group consisting of olefins, dienes, aromatic hydrocarbons, acrylates, and alcohols. (See, for example, EP 1,694,771B1). An example includes core-shell polymers, wherein the core is composed of a rubbery polymer and the shell is composed of a styrene copolymer (see, for example, U.S. Patent No. 5,321,056, which is incorporated herein by reference.) Other examples include core-shell and functional polyolefins, such as those described in US2014 / 0256848 A1 incorporated herein by reference. See also EP 2 139 948 B1.
[0105] In embodiments, examples of commercially available impact modifiers may include, but are not limited to, ethylene / propylene terpolymers; functionalized polyolefins such as those containing methyl acrylate and / or glycidyl methacrylate; styrene-based block copolymer impact modifiers; and various acrylic core / shell impact modifiers. Residues of such additives are also contemplated as being part of the polyester composition.
[0106] It should also be noted that certain friction additives may also function as impact modifiers. Thus, in certain embodiments, it is contemplated that an additive identified as a friction additive may be included as an impact modifier in addition to one of the other identified friction additives. For example, Modiper 4300 may be used as an impact modifier and may be added with a wax additive such as Licowax OP, where Licowax OP is a component (b) additive and Modiper 4300 is a component (c) additive.
[0107] Commercially available examples include:
[0108] 4300 and 4400, available from Nippon Oil & Fat Corporation;
[0109] Kane M300, available from Kaneka Americas Holding, Inc.;
[0110] Kane B564, available from Kaneka Americas Holding, Inc.;
[0111] Kane ECO 1000, available from Kaneka Americas Holding, Inc.;
[0112] Kane MR02, available from Kaneka Americas Holding, Inc.;
[0113] Kane MR03, available from Kaneka Americas Holding, Inc.; and
[0114] 8900, available from Arkema.
[0115] The impact modifiers of component (c) described above may be present in an amount of 0.5 to about 15 weight percent. In other embodiments, they are present in an amount of 0.5 to 14, or 0.5 to 12, or 0.5 to 10, or 0.5 to 8, or 0.5 to 6, or 0.5 to 5, or 0.5 to 4, or 0.5 to 3, or 0.5 to 2, or 0.5 to 1, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 5, or 1 to 4, or 1 to 3, or 1 to 2, or 2 to 14, or 2 to 12, or 2 to 15, or 2 to 16, or 2 to 17, or 2 to 18, or 2 to 20, or 2 to 19, or 2 to 21, or 2 to 22, or 2 to 24, or 2 to 26, or 2 to 27, or 2 to 28, or 2 to 29, or 3 to 40 ... or 4 to 12, or 4 to 10, or 4 to 8, or 4 to 6, or 4 to 5, or 5 to 14, or 5 to 12, or 5 to 10, or 5 to 8, or 5 to 6, or 6 to 14, or 6 to 12, or 6 to 10, or 6 to 8 weight percent.
[0116] In an embodiment, the polyester composition comprises 0.1 to 5 wt % of component (b) and 1 to 10 wt % of component (c), or 0.5 to 4 wt % of component (b) and 2 to 8 wt % of component (c), or 0.5 to 2.5 wt % of component (b) and 3 to 6 wt % of component (c), or 1 to 2 wt % of component (b) and 3.5 to 5.5 wt % of component (c), based on the total weight of the polyester composition. In an embodiment, component (b) comprises siloxane, and component (b) comprises ethylene acrylate terpolymer. In an embodiment, component (b) comprises siloxane, and component (b) comprises ethylene, acrylic acid and (meth) acrylate glycidyl terpolymer. In one embodiment, component (b) comprises Genioplast S, and component (b) comprises Lotader 8900. In one embodiment, the polyester composition comprises DX4000 or DX4001 in an amount of 93 to 95 wt%, Genioplast S in an amount of 1 to 2 wt%, and Lotader 8900 in an amount of 4 to 5 wt%.
[0117] The present invention can be further illustrated by the following examples or preferred embodiments thereof, but it should be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the present invention unless otherwise specifically stated.
[0118] Experimental Section
[0119] Part 1. Base resin testing
[0120] A series of tests were performed on several commercially available resins. This test was designed to benchmark the performance of copolyester compositions with respect to physical properties and friction performance.
[0121] Physical properties typically reported in the Technical Data Sheet (TDS) were evaluated using injection molded tensile or flexural bars using established test methods as defined by ASTM. For commercially available resins, molding was performed using the drying and processing conditions reported on the Technical Data Sheet. For modified resins, the processing conditions used were selected using the processing conditions of the base resin.
[0122] Multiple tests were completed on all samples and modified resins as detailed in Section 3 below. These test methods are broken down as follows:
[0123] ●Specific physical properties are usually found in the technical data sheet. Specific tests include tensile properties (ASTM D638), flexural properties (ASTM D790), notched Izod impact properties (ASTM D256) and heat deformation properties (ASTM D648). In all cases, commercial resins and modified resins follow standard conditioning and testing protocols.
[0124] The friction profile of the base resin, reported as static and dynamic coefficients of friction (μ s and μ k ). These values were measured using a Bruker Tribometer by intentionally contacting the surface of a pair of 4"x4"x1 / 8" plates produced using injection molding. Gloves were worn at all times to avoid direct contact with the test specimens to avoid contaminating the friction data measurements. Once molded, the coefficient of friction was measured using a pair of plates according to the following definition:
[0125] ○Static COF(μ s ), the contact force between the two plates (F z ) and the relative velocity between the two contacting plates (v x ) are close to zero, for example:
[0126] ■F z =0.05N,v x =0.01mm / s
[0127] ○ Dynamic COF (μk), defined as the friction force measured between two contacting plates at constant force and relative velocity, for example:
[0128] ■F z =3.00N, v x =10.0mm / s
[0129] A summary of the commercial resins evaluated as "control" or "counter" examples is shown in Table 1 below.
[0130] Table 1. Summary of “control” or “comparative” materials evaluated
[0131]
[0132] A summary of the physical properties of the control / comparative materials is shown in Table 2 below.
[0133] Table 2 - Summary of physical properties of the materials in Table 1.
[0134]
[0135]
[0136] Review of the physical property data in Table 2 reveals that resins C-01 and C-02 (ABS and polycarbonate (PC), respectively) exhibit higher stiffness in tensile and flexural modulus than all other materials evaluated. In addition to modulus, resin C-03 (a cellulosic material) exhibits similar tensile properties compared to C-01, as well as impact toughness of similar magnitude as measured by notched Izod testing. Resins C-06, C-07, C-09, and C-10 have significantly higher notch sensitivity than C-01, while resins C-04, C-05, and C-08 have the lowest stiffness of the commercial resins evaluated.
[0137] The friction properties of the materials in Table 1 were evaluated to quantify the static and kinetic friction coefficients (μ s and μ k ). The coefficient of friction (COF) values are listed in Table 3 below.
[0138] Table 3. Summary of friction characteristics:
[0139]
[0140] Inspection of Table 3 shows that C-01 (ABS) and C-02 (PC) have similar friction profiles when measured according to a skateboard-type test, referring to the coefficient of static friction and the coefficient of dynamic friction (Table 3). In addition, resin C-01 provides lower friction performance than all of the resins evaluated. Therefore, in order to achieve the functionality of applications that previously used ABS materials and required similar friction behavior, it will be necessary to modify the friction performance of other resins (e.g., C-03 to C-10) to match the performance of C-01 in the friction test, while still maintaining (or not significantly reducing) the physical properties, most notably stiffness and impact toughness, compared to the unmodified base resin.
[0141] Part 2. Modification
[0142] Modified development samples were generated using twin screw compounding and various additives to modify properties, most notably by incorporating various additives to modify the friction profile. These additives can vary in chemistry, ranging from short chain molecules (e.g., waxes) to high molecular weight or ultra-high molecular weight organosiloxanes (e.g., PDMS). In the composite formulations, it was found that the additives could act as internal and / or external lubricants, depending on the specific additive chemistry, molecular weight, loading level, and function. The additives used are listed in Table 4 below.
[0143] Table 4. Additives used to modify resins
[0144] sample additive T-01 Tegomer H-Si 6441 P T-02 Genioplast S T-03 DowSil 4-7081 T-04 Loxiol P861 T-05 3M PM-870 T-06 Incromax 100 T-07 Tegomer V-Si 4042 T-08 Tegomer M-Si 2650 T-09 Tegomer E-Si 2330
[0145] In addition to the above additives, other additives that can be incorporated into potential formulations are additives specifically designed to modify impact toughness. Additives for impact modification are typically incorporated at loading levels below 15 wt. %, and cover a variety of chemistries and forms, including: core-shell, branched, reactive, MBS, acrylic, EGMA, etc. Impact modifiers tested alone or in combination with additives (from Table 4) are listed in Table 5 below.
[0146] Table 5. Impact Modification Additives
[0147] sample additive I-01 Modiper 4300 I-02 Modiper 4300 I-03 M300 I-04 B564 I-05 ECO 100 I-06 Lotader 8900
[0148] Part 3. Examples
[0149] Various copolyester samples containing TMCD and EG were produced by modification with friction additives and / or impact modifiers, such as Eastman GMX201 (sample C-06), Tritan TM DX4001 (sample C-07) and Tritan TM DX4000 (Sample C-10). Physical properties were measured before and after the heat aging regimen. The friction performance of some formulations was also evaluated using a tribometer (as discussed above). The results are reported in the table below, which summarizes the performance of the modified formulations compared to the control examples.
[0150] Table 6 summarizes the formulations evaluated in this study, namely, GX-01 to GX-35 using sample C-06 as the base resin, DX-01 to DX-21 using sample C-07 as the base resin, and DX-22 to DX-30 using sample C-10 as the base resin. The specific composition of the friction additives compared to the control or comparative example is listed. It should be noted that although the modified Tritan TM The "base resin" used in the sample is Tritan TM GMX201(C-06), Tritan TM DX4001(C-07), Tritan TM DX4000 (C-10), but the experience of this study will help understand other TMCD and EG base resins (e.g., Tiltan TM GMX200) usage.
[0151] Table 6. Summary of exemplary formulations evaluated
[0152]
[0153]
[0154]
[0155]
[0156] The physical properties and performance of all exemplary resins were measured according to the same procedures and test methods mentioned above for all control, comparative and / or commercial resins. A summary of the physical properties of all exemplary resins - most notably tensile properties, notched Izod impact toughness, flexural modulus and heat distortion temperature - is shown in Table 7.
[0157] Table 7. Summary of TDS properties of exemplary formulations:
[0158]
[0159]
[0160]
[0161]
[0162] Table 7 shows the performance of the exemplary formulations relative to existing commercial formulations. Review of Table 7 revealed the following unexpected properties:
[0163] A range of formulations with different COF additive types and loading levels maintained or exceeded elongation at break compared to unmodified copolyester resins (C-06 or C-07)
[0164] Most of the exemplary formulations showed less than 10% decrease in tensile yield compared to the control copolyester samples (C-06 and C-07), while meeting or exceeding the performance of C-1
[0165] ● Compared with C-06 and C-07, the notched Izod impact energy has been greatly improved - both the failure mode (no fracture) and the impact energy - far exceeding C-01
[0166] ●For all formulations, the heat distortion temperature decreases minimally relative to the unmodified copolyester samples (C-06 or C-07), with performance comparable to C-01
[0167] ●Can improve the notched Izod fracture type from complete fracture to no fracture (reduced notch sensitivity) without the use of impact modifiers (e.g., DX-18, DX-22)
[0168] ● Ability to use friction modifiers (e.g., DX-17, DX-18, DX-19, DX-20, DX38, DX-39, DX-40, DX-41, DX-42) to increase tensile and flexural moduli
[0169] Physical properties were also evaluated after a simple accelerated aging protocol. This was accomplished by subjecting all samples to a heat aging protocol and then testing the heat aged test bars for physical properties according to the standard ASTM test methods as summarized previously. The goal of completing the testing before and after heat exposure was to determine if any substantial changes in performance and physical properties resulting from the friction modifiers and additives were observed in the modified copolyester examples. Table 8 summarizes the tensile properties measured after standard conditioning (72 hours at 23°C and 50% RH) and heat aging protocols (200 hours at 60°C).
[0170] Table 8. Summary of TDS properties of exemplary formulations after heat aging.
[0171]
[0172]
[0173]
[0174] Review of Table 8 reveals that the changes in tensile properties are generally small with the exception of GX-33, GX-34, GX-35 and GX-36 and unmodified copolyester sample C-07 compared to sample C-01 and unmodified copolyester sample C-06. GX-33 and GX-34 contain T-01, while GX-35 and GX-36 contain T-01 and I-06. The inclusion of T-01 appears to unexpectedly significantly accelerate aging, while further addition of I-06 appears to further accelerate aging of the GX copolyesters. This same phenomenon is not observed when DX4001 is used as the copolyester, as observed in samples DX-17, DX-18, DX-19 and DX-20. The modified copolyester samples showed a decrease in impact toughness in all samples evaluated after aging, however, with the exception of GX-33, GX-34, GX-35, and GX-36, the performance of the modified samples in terms of failure mode and impact energy still far exceeded that of the unmodified copolyesters (C-06, C-07). Not all combinations of copolyesters, friction modifiers, and impact modifiers resulted in a minor decrease in performance.
[0175] Finally, the friction performance of certain modified samples of GMX201 and DX4001 were compared to control samples C-06 and C-07. The results are listed below in Table 9. Table 9 also includes % haze data for certain DX4001 samples.
[0176] Table 9. Summary of friction / haze properties of DX4000.
[0177]
[0178]
[0179] Reviewing Table 9, it is found that the inclusion of impact modifier I-06 increases the static and kinetic friction of samples GX-17 and GX-18 compared to C-06, and increases the static and kinetic friction of samples DX-11 and DX-12 compared to C-07. This same phenomenon is observed when I-06 is used in addition to friction modifier T-02, where the static and kinetic friction of samples GX-38 and GX-39 increases compared to GX-36 and GX-37, and the static and kinetic friction of samples DX-23 and DX-24 increases compared to DX-21 and DX-22. However, a synergistic effect of friction modifier T-03 and impact modifier I-06 is unexpectedly observed in samples DX-25, DX-26, DX-27, and DX-28. In these samples, a further reduction in static and dynamic friction was observed by adding the impact modifier I-6 compared to the addition of friction modifier T-03 alone. The same effect was not observed when GMX201 was used as the copolyester, as shown in samples GX-40, GX-41, GX-42, and GX-43. In addition, the inclusion of impact modifier I-06 with friction modifier T-1 had no effect on friction compared to GX-32 and GX-33, as shown in samples GX-34 and GX-35; and for samples DX-19 and DX-20, the inclusion of impact modifier I-06 with friction modifier T-1 had no effect on friction compared to DX-17 and DX-18. This unexpected phenomenon may provide a way to create / configure materials with tunable friction and impact properties, particularly to provide low friction and high impact properties that exceed C-01. Further inspection of Table 9 reveals that the haze values for samples using T-1, T-7, T-8, and T-9 are unexpectedly low, providing a high clarity material with similar friction to C-01.
[0180] The invention has been described in detail with particular reference to certain embodiments thereof, but it will be understood that variations and modifications can be effected within the spirit and scope of the invention.
Claims
1. A polymer composition comprising: (a) a copolyester comprising: (i) dibasic acid residues comprising from about 90 to 100 mole percent terephthalic acid residues and from 0 to about 10 mole percent isophthalic acid residues; and (ii) diol residues comprising from 58 to 95 mole percent ethylene glycol residues; and from 5 to 42 mole percent 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, wherein the copolyester comprises a total of 100 mole percent of the dibasic acid residues and a total of 100 mole percent of the diol residues; (b) from about 0.1 to about 12 weight percent of a friction additive selected from waxes and silicones; and (c) from about 0.5 to about 15 weight percent of at least one impact modifier.
2. The composition of claim 1 wherein the friction additive is a wax.
3. The composition of claim 2, wherein the friction additive is present in an amount of about 0.1 to about 3 weight percent.
4. The composition of claim 1 wherein the friction additive is a silicone.
5. The composition of claim 4, wherein the friction additive is present in an amount of about 0.1 to about 7 weight percent.
6. The composition of claim 4, wherein the friction additive is a polyester-modified siloxane.
7. The composition of claim 4, wherein the friction additive is a non-reactive silicone.
8. The composition of claim 4, wherein the friction additive is an aryl-modified siloxane.
9. The composition of any one of claims 1 to 8, wherein the polyester composition is a copolyester comprising diol residues comprising 10 to 42 mole percent TMCD residues and 58 to 90 mole percent EG residues.
10. The composition of claim 9, wherein the polyester composition is a copolyester comprising diol residues comprising 20 to 30 mole percent TMCD residues and 70 to 80 mole percent EG residues.
11. The composition of claim 9, wherein the polyester composition is a copolyester comprising diol residues comprising 30 to 40 mole percent TMCD residues and 60 to 70 mole percent EG residues.
12. The composition of any one of claims 1 to 11, wherein the composition comprises: (a) 5 to 95 weight percent of the copolyester (a); and (d) 5 to 95 weight percent of at least one polymer component other than (a).
13. The composition of claim 12, wherein (d) is selected from the group consisting of polyamides; polystyrene; styrene acrylonitrile; acrylonitrile butadiene styrene; poly(methyl methacrylate); acrylics; poly(ether-imides); polyamides; polystyrene; polystyrene copolymers; styrene acrylonitrile copolymers; acrylonitrile butadiene styrene copolymers; poly(methyl methacrylate); acrylic copolymers; poly(ether-imides); polyphenylene ether; poly(phenylene ether) / polystyrene blends; polycarbonates; poly(ester-carbonates); polyphenylene sulfide / sulfone; polysulfone; polysulfone ether; and poly(ether-ketone) or mixtures thereof.
14. The composition of any one of claims 1 to 13, wherein the composition has a static COF of 0.6 or less and a dynamic COF of 0.5 or less.
15. The composition of any one of claims 1 to 14, wherein the composition has a haze of 5% or less.
16. The composition of any one of claims 1 to 15, wherein the composition has a b* of 6 or less.
17. The composition of any one of claims 1 to 16, wherein the composition comprises additional additives selected from antioxidants, heat stabilizers, mold release agents, antistatic agents, brighteners, colorants, flow aids, processing aids, plasticizers, anti-fog additives, minerals, UV stabilizers, lubricants, chain extenders, nucleating agents, reinforcing fillers, other fillers, glass fibers, carbon fibers, flame retardants, dyes, pigments, colorants, additional resins, and combinations thereof.
18. A shaped or formed article comprising the polymer composition according to any one of claims 1 to 17.
19. The article according to claim 18, wherein the article is selected from an extruded article, a calendered article and / or a molded article.
20. The article of claim 19, wherein the article is selected from the group consisting of injection molded articles, extruded articles, cast extruded articles, profile extruded articles, melt spun articles, thermoformed articles, extrusion molded articles, injection blow molded articles, injection stretch blow molded articles, extrusion blow molded articles, and extrusion stretch blow molded articles.
Citation Information
Patent Citations
Processes for dispersing an impact modifier in a macrocyclic polyester oligomer
EP1694771B1
Polyester compositions, method of manufacture, and uses thereof
EP2139948B1
Impact-modified polycarbonate / polyester or polycarbonate / polyamide compositions
US20140256848A1
Process for preparing aromatic diester containing copolyesters and products obtained thereby
US3772405A
Amorphous, aromatic polyester containing impact modifier
US5321056A